Про вплив скінченних початкових деформацій на поверхневу нестійкість нестисливого пружного шару, що взаємодіє з півпростором в’язкої стисливої рідини - Багно, О.М. (Доповіді НАН України, 2021)
Розглядається задача про поширення квазілембових хвиль у попередньо деформованому нестисливому пружному шарі, що взаємодіє з півпростором в'язкої стисливої рідини. Дослідження проводиться на основі тривимірних лінеаризованих рівнянь теорії пружності скінченних деформацій для нестисливого пружного шару і тривимірних лінеаризованих рівнянь Нав’є—Стокса для півпростору в'язкої стисливої рідини. Застосовуються постановка задачі та підхід, засновані на використанні представлень загальних розв’язків лінеаризованих рівнянь для пружного тіла і рідини. Отримано дисперсійне рівняння, яке описує поширення нормальних хвиль у гідропружній системі. Побудовано дисперсійні криві квазілембових хвиль у широкому діапазоні частот. Проаналізовано вплив скінченних початкових деформацій у нестисливому пружному шарі, а також півпростору в'язкої рідини на фазові швидкості, коефіцієнти загасання, дисперсію квазілембових мод і поверхневу нестійкість гідропружного хвилеводу. Числові результати представлені у вигляді графіків і дано їх аналіз. The problem of the propagation of quasi-Lamb waves in a pre-deformed incompressible elastic layer that interacts with the half-space of an viscous compressible fluid is considered. The study is conducted on the basis of the three-dimensional linearized equations of elasticity theory of finite deformations for the incompressible elastic layer and on the basis of the three-dimensional linearized Navier–Stokes equations for the half-space of a viscous compressible fluid. The problem formulation and the approach, which are based on the utilization of representations of the general solutions of the linearized equations for an elastic solid and a fluid, are applied. Next, applying the Fourier method, we arrive at three eigenvalue problems for the equations of motion of the elastic body and the fluid. Solving them, we find the eigenfunctions. Substituting the general solutions into the boundary conditions, we obtain a homogeneous system of linear algebraic equations for the arbitrary constants. From the condition for the existence of a nontrivial solution, we derive the dispersion equation. It describes the propagation of normal waves in the hydroelastic system. The dispersion curves for quasi-Lamb waves over a wide range of frequencies are constructed. The effect of the finite initial deformations in an elastic layer, the thickness of the elastic layer, and the half-space of viscous compressible fluid on the phase velocities, attenuation coefficients, and dispersion of quasi-Lamb modes are analyzed. It follows from the graphical material presented above that, in the case of compression with 0.54, i.e., with a 46–percent reduction in the length of the highly elastic incompressible body, the phase velocities of the surface waves (Stoneley waves and Rayleigh waves) vanish. This indicates that the surface instability develops at 0.54 for a highly elastic incompressible non-Hookean body initially in a plane stress-strain state. We should point out that these figures agree with results obtained earlier in the theory of stability and correspond to the critical value of the con-traction parameter. In the case of highly elastic incompressible bodies, the linearized wave theory makes it possible to study not only general and several specific wave processes, but also the conditions under which the surface instability begins in elastic bodies and hydroelastic systems. It also follows from the graphs that the viscous fluid slightly affects the surface instability of hydroelastic systems. The numerical results are presented in the form of graphs, and their analysis is given.